Opinion of Mothers in the Acceptor Family Planning Program who are Less Interested in Choosing the Intrauterine Contraceptive Device (IUD) Method - Suave Barreto, Celsea; Barreto Amaral, Meriana; Komanng Satriyasa, Bagus; Guterres Correia, Avelino; Corte Real de Araujo, Artur Natalino; Rosario Pacheco, Cipriano do (Rifa'Institute, 2025)
Introduction: Aseptor LTCM (long-term contraceptive method) is still not sufficient because the community’s knowledge is still minimal about the advantages and disadvantages, limitation of trained personnel, and existing installation. One of the LTCM is the intrauterine device contraceptive method, which is a long-term method that is effective when giving a child space. Objective: To explore the opinions of mother acceptors of family planning who have less interest in choosing the intrauterine device (IUD) contraceptive method Method: This research uses a qualitative and exploratory descriptive method. The data collection technique is non-probability sampling. The total sample consists of 10 people. Result and Discussion: The results from the 10 respondents, who clarified their knowledge, perceptions, and opinions about the Intrauterine Device (IUD) contraceptive method, show that while the respondents are generally familiar with the IUD method, some have negative perceptions about it. These perceptions are often influenced by family members and colleagues. Additionally, some respondents have negative views of the IUD method because of information they have heard in the community, which often causes fear. As a result, they have no intention or desire to use the IUD method. Therefore, health professionals need to provide accurate and clear guidance to mothers so they can fully understand the IUD method. Conclusion: It is concluded that mothers who accept family planning are aware of the advantages and disadvantages of the IUD method. This is why some mothers have negative perceptions and ideas about the IUD method.